PENGARUH PENGGUNAAN BARIER NET BERWARNA (MERAH DAN PUTIH) TERHADAP POPULASI Bemisia tabaci PADA TANAMAN CABAI RAWIT (Capsicum frutescens L.) DI DESA KERTA - Astuthi, Made Mika Mega; Sudiarta, I Putu; Nyana, I Dewa Nyoman; Suastika, Gede (Journal of Agricultural Science and Biotechnology, 2015)
The research about impact of using barrier of net color (red and white) for whitefly population on cayenne pepper plant in Kerta Village was conducted in order to know firstly about species of whitefly that existing on the cayenne pepper, secondly to know about impact of net color for populations of whitefly on the cayenne papper. The research was done using the randomized block design (RBD) with 3 treatments and 9 replications. The observation covered of the population of whitefly and symptom of virus infection. The results of this research showed whitefly were identified as Bemisia tabaci . The result indicated the lowest average populations of B emisia tabaci occurred in the white net barrier treatment.
Keywords: cayenne pepper, net, Bemisia tabaci